PERANCANGAN VIDEO COMPANY PROFILE SEBAGAI MEDIA PROMOSI DAN INFORMASI PADA TOKO CITRA MEUBEL SEMARANG - Fajar Kusumo; Sulartopo Sulartopo (Pixel :Jurnal Ilmiah Komputer Grafis, 2019)
Meubel's image which was formerly named "Mukti Jaya" then changed its name to mid of 2013 is one of the companies engaged in furniture trade, from production to buying and selling, which is located in Semarang, precisely on Jl. Elephant No. 188 Ruko No. 9 Semarang Java Central, established on November 22, 1998. Current promotions is using brochures, MMT banners, through the radio, posting advertisements on forums buying and selling and exhibition. However, with the above promotional media less promotion effective because brochures, banners, exhibits have the nature of direct marketing less reach and the ability of the imagination of readers to enjoy and understand it, radio advertisements that have a time limit, and are constrained deeply presentation to the customer because of the less specific promotional media introduced product. Based on the weaknesses above, the company profile video is used for complete brochures, MMT banners, radio ads, and buying and selling forums. Overall it can be concluded that the researchers have succeeded implementing a media company profile that can complement that promotion already running. This can be seen from the results of the validation test conducted by expert experts that overall, the company profile that has been developed by researchers entered into a very good category with a percentage of 90.8%. Other than that, through a field test represented by 30 respondents it can be concluded that Overall, this media has been developed by researchers into the category very good with a percentage of 84.6%.